Implementasi Nilai-Nilai Sufisme Tarekat Naqsyabandiyah di Sulawesi Selatan - Hadarah Rajab (Universitas Islam Negeri Mataram, 2010)
For Muslims, especially those who are interested in sufism, Naqsabandiya sufi order is of special interest due to its important position in society. This is also because the great influence that this sufi order has played in the Islamic world, especially in Indonesia, India, China and Middle East. In Indonesia, this sufi order has spread throughout the islands, including in South Celebes. One of the great teacher of this sufi order came from this region, namely Syaikh Yusuf al-Makassari. He was believed to be the first to introduce this sufi in Indonesia. This essay attempts to explain the method of essential teaching developed in this sufi order, as this is practiced by people in South Celebes. It also traces the sufi’s historical background and expounds the ways in which it influences people’s social life, including in the fields of worship and human relations.